SEMINAL PROTEINS PROFILE BY GRADIENT SDS-PAGE ELECTROPHORESIS IN NARI SUWARNA RAMS - KAIMAL, PRATHIBHA; TANDLE, M K; SELVARAJU, S (The Indian Journal of Animal Reproduction, 2022)
A study on seminal proteins profile using 6-16% gradient SDS-PAGE electrophoresis was conducted in NARI Suwarna rams. The majority of seminal plasma proteins were observed to be less than 100 kDa. Among these 26 kDa were abundant followed by 68 kDa and 23 kDa proteins. Identification of these proteins will be useful in relating the semen quality and fertility.